HOMECARE APOTEKER SEBAGAI SARANA PENINGKATAN PENGETAHUAN MASYARAKAT DESA SEGALA ANYAR LOMBOK TENGAH - Lalu Iman Saptahadi; Baiq Reni Pratiwi (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
The shift in pharmacy profession from drug-oriented to patient-oriented necessitates pharmacists always providing the best possible service to their customers. It is the obligation of pharmacists to offer patients with accurate medication therapy information. Home care is one type of pharmaceutical assistance provided by pharmacists. Direct visits to the patient's house for home care activities will have a greater impact on the patient's understanding of the disease and its treatment. Home care activities were conducted in the village of all new Central Lombok with a total of 30 patients by local pharmacists and postgraduate students from the University of Qamarul Huda Badaruddin Bagu. The activity begins with a direct interview, followed by the completion of a questionnaire on the patient's understanding of the ailment and its treatment options. The patient's response is based on the results of routine homecare.